2021
DOI: 10.3390/ijms22115599
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Hyaluronidase and Spiperone as a Potential Treatment for Pulmonary Fibrosis

Abstract: Concentration of hyaluronic acid (HA) in the lungs increases in idiopathic pulmonary fibrosis (IPF). HA is involved in the organization of fibrin, fibronectin, and collagen. HA has been proposed to be a biomarker of fibrosis and a potential target for antifibrotic therapy. Hyaluronidase (HD) breaks down HA into fragments, but is a subject of rapid hydrolysis. A conjugate of poloxamer hyaluronidase (pHD) was prepared using protein immobilization with ionizing radiation. In a model of bleomycin-induced pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Moreover, with the increasing understanding of the IPF mechanism, more and more potential therapeutic targets have been discovered, such as MMPs, 104 glycosaminoglycan, 105 non-coding RNA, 106 adenosine, 107 mechanosensitive MDM4, 108 micellar hyaluronidase, and spiperone. 109 So far, many researchers have focused on the downstream effectors of gene expression, such as cytokines and enzymes. The epigenetic modification also plays a vital role in IPF.…”
Section: Perspectivesmentioning
confidence: 99%
“…Moreover, with the increasing understanding of the IPF mechanism, more and more potential therapeutic targets have been discovered, such as MMPs, 104 glycosaminoglycan, 105 non-coding RNA, 106 adenosine, 107 mechanosensitive MDM4, 108 micellar hyaluronidase, and spiperone. 109 So far, many researchers have focused on the downstream effectors of gene expression, such as cytokines and enzymes. The epigenetic modification also plays a vital role in IPF.…”
Section: Perspectivesmentioning
confidence: 99%
“…Энзимотерапия при заболеваниях глаза описана в литературе, однако большого количества исследований и публикаций не наблюдается [16]. Применение иммобилизированных форм гиалуронидазы (ИГ) и субтилизина (ИС) для офтальмологической практики представляются весьма перспективным, поскольку их фармакологическое действие отслеживает многие патогенетические механизмы заболеваний глаза [17][18][19][20].…”
Section: резюмеunclassified
“…The main enzyme that regulates HA metabolism is hyaluronidase (HD), which remodels the extracellular matrix by cleaving HA into fragments (glucosamines and glucuronic acid) [ 13 , 14 ]. Given the role of HA in the organization of fibrin, fibronectin, and collagen, it is considered one of the biomarkers of fibrosis and a potential target for antifibrotic therapy, in particular for drugs based on HD [ 15 ]. The pathogenesis of pulmonary fibrosis is complex and not fully understood, which hinders the development of specific therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we investigated the effects of poloxamer hyaluronidase (pHD—a conjugate of Pluronic L31 and hyaluronidase) compared to native HD in a model of bleomycin-induced pulmonary fibrosis in C57BL/6 mice. It was shown that the administration of pHD reduced the content of connective tissue in the lung by more than twofold, and decreased the concentration of TGF-β, hydroxyproline, type 1 collagen, and total collagen in the lung homogenate [ 15 ].…”
Section: Introductionmentioning
confidence: 99%